2014
DOI: 10.1186/1745-6215-15-234
|View full text |Cite
|
Sign up to set email alerts
|

National Adolescent Treatment Trial for Obesity in Kuwait (NATTO): project design and results of a randomised controlled trial of a good practice approach to treatment of adolescent obesity in Kuwait

Abstract: BackgroundFew randomised controlled trials (RCTs) of interventions for the treatment of adolescent obesity have taken place outside the western world. This RCT tested whether a simple ‘good practice’ intervention for the treatment of adolescent obesity would have a greater impact on weight status and other outcomes than a referral to primary care (control) in adolescents in Kuwait City.MethodsWe report on an assessor-blinded RCT of a treatment intervention in 82 obese 10- to 14-year-olds (mean age 12.4, SD 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 24 publications
(39 reference statements)
0
31
0
1
Order By: Relevance
“…One of the findings of the NATTO was poor engagement with treatment, as evidenced by the poor attendance of families in both the intervention and control arms of the trial 18. Therefore, findings from the present study might have been useful to demonstrate to the adolescents and their families that their obesity was a medical problem, and so possibly persuade them to engage more with treatment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…One of the findings of the NATTO was poor engagement with treatment, as evidenced by the poor attendance of families in both the intervention and control arms of the trial 18. Therefore, findings from the present study might have been useful to demonstrate to the adolescents and their families that their obesity was a medical problem, and so possibly persuade them to engage more with treatment.…”
Section: Discussionmentioning
confidence: 77%
“…We recruited 80 obese adolescents participating in the NATTO in Kuwait City18 at the preintervention stage of the trial. They were all at or above the age- and sex-adjusted 95th body mass index (BMI) percentile, which defines obesity 19.…”
Section: Methodsmentioning
confidence: 99%
“…Mean change in BMI z-score were not significantly better in the intervention compared to the control arm of these studies (−0.20 to 0.0 s.d) [20, 41, 49]. Resnicow (2015) [35] was able to find some changes in lower intensity intervention groups: mean change BMI percentile from baseline was −1.8 for usual care, −3.8 for PCPs care, and −4.9 for PCP and RD care.…”
Section: Review Processmentioning
confidence: 92%
“…Several studies showed that lower intensity interventions were less effective [20, 35, 41, 49]. Mean change in BMI z-score were not significantly better in the intervention compared to the control arm of these studies (−0.20 to 0.0 s.d) [20, 41, 49].…”
Section: Review Processmentioning
confidence: 99%
See 1 more Smart Citation